Changes in Serum Levels of Lipid Profile Parameters and Proteins in Toxoplasma gondii Seropositive Patients - Hayder Z. Ali; Harith Saeed Al-Warid (Iraqi Journal of Science, 2021)
The influence of Toxoplasma gondii on some biochemical parameters has lately gained an increasing attention. The aim of this study was to assess the levels of some biochemical parameters in Toxoplasma positive and negative subjects. An analytical case–control study was achieved in Baghdad for the period from October 2018 until March 2019. Forty nine females participated in this study, with an age range of 18-55 years. The participants were separated into two groups, namely Toxoplasma positive subjects (n=21) and Toxoplasma negative subjects (n=28), based on enzyme-linked immunosorbent assay (ELISA). Blood and serum samples were collected from all subjects to evaluate the serum levels of cholesterol, triglycerides, high density lipoprotein (HDL), very low density lipoprotein (VLDL), low density lipoprotein (LDL), total protein, total globulin and total albumin. The results showed non-significant differences between Toxoplasma positive and negative subjects for all the parameters, although cholesterol levels were lower (mean 149 mg/dL; range 131.9-165.9 mg/dL) in Toxoplasma positive patients as compared to those in Toxoplasma negative subjects (161 mg/dL; 146.7-175 mg/dL). In addition, triglycerides levels were lower (160 mg/dL; 123.3-196.8 mg/dL) in Toxoplasma positive subjects as compared to the control subjects (165mg/dL; 134.2-195.3 mg/dL). The only significant difference was noticed among subjects with an age range of 26-35 years, where globulin level was significantly higher (p=0.023) in Toxoplasma negative subjects as compared to that in Toxoplasma positive subjects.